Diseño de una ruta turística en el cantón San Lorenzo, Provincia de Esmeraldas, año 2021 - Palma Chuquian, Maria Fernanda (2021)
The San Lorenzo canton is closely related to nature, endowed with high biodiversity, in a variety of ecosystems that extend in an area with a high index of endemic species. Through the years its commercial tradition has been preserved, and currently in its fundamentally economic process, it is committed to tourism. A tourist route in the San Lorenzo canton promotes its attractions and reflects the sense of tourism through the use of all its resources to make a true tourist experience with multiple benefits for the canton and the province of Esmeraldas. In Ecuador, as in the rest of the world, the economic crisis after the pandemic directly affected the registration of visits for tourism. It is frequent that the routes that were planned and positioned as tourist destinations in various territories of the country were affected. The innovative design of new routes can contribute to mitigating this problem that is found in the most unprotected sectors in the province of Esmeraldas in the canton of San Lorenzo A tourist route in the San Lorenzo canton will allow a visitor or tourist to have a guide to be able to have direct contact with the service providers or with the visit records that can be given in the different attractions. In addition to integrating the people who reside in these attractions in order to promote sustainable tourism. This research contributes to the strengthening of tourism in the province of Esmeraldas, especially in the San Lorenzo canton, one of the most vulnerable Catons due to COVID-19 and that has the possibility of recovering and reactivating its economy.